A rare case of lyell syndrome secondary to ofloxacin eye drops - Anusree Vellot Sreedharan; Kikkeri N Naveen; Sowmyashree Krishna; Sweta R Prabhu (Wolters Kluwer Medknow Publications, 2023)
Lyell syndrome or toxic epidermal necrolysis (TEN) is a severe mucocutaneous adverse drug reaction characterized by generalized erythema and widespread epidermal necrosis resulting in its detachment. If not appropriately intervened, it may result in sepsis, multiorgan failure, and death. TEN secondary to topical drugs is very rare and only a few cases have been documented so far. Here, we report a case of a 10-year-old child who presented with features of TEN following administration of ofloxacin eye drops, which is commonly prescribed in ophthalmic practice for conjunctival inflammation. She was treated in the pediatric intensive care unit with systemic corticosteroids, cyclosporine, intravenous immunoglobulin, and other supportive therapy including collagen dressing, and showed complete recovery. This case report highlights the need for awareness among physicians regarding serious adverse events caused by topical drugs and a multidisciplinary approach which paves the road for recovery.